Einwilligungserklärung und Forschungsinformation zur Gewinnung tierischer Proben erarbeitet im Auftrag der Nationalen Forschungsplattform für Zoonosen - Goebel, Jürgen W. (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2012)
" Infectious agents that can be transmitted from animals to humans and cause so-called zoonoses are the subject of numerous research projects. In order to better understand, combat and monitor these pathogens, animal samples are taken for scientific studies. In this context, legal and data protection issues arise that are the subject of this legal expertise. It serves to give researchers legal certainty when taking and processing animal samples as well as when creating research information and declarations of consent. The book explains which legal issues are affected in the scientifically relevant sampling scenarios and in the further processing of sample accompanying data. The range of topics extends from the obligation to notify and report animal diseases to usage and exploitation rights to the samples."